The impact of country-of-origin image on brand loyalty: evidence from Iran. Issue 4 (12th September 2016) - Esmaeilpour, Fariba; Abdolvand, Mohammad Ali
Abstract : Purpose: The purpose of this paper is to examine the effects of country-of-origin (COO) image on brand attitude and brand loyalty of Generation Y's consumers toward two categories of luxury fashion brands. Design/methodology/approach: First, a structural equation modeling method was employed based on data collected from 419 individuals born between 1977 and 1994 in Iran. In next steps, analysis was conducted using hierarchical regression analysis with a two-way interaction and a slope analysis. Watches and sunglasses are two luxury product categories chosen in this study. Findings: The findings of the study reveal that consumers' perception from COO technology advancement is the determinant of attitude toward luxury brands. COO technology advancement also, mediated by brand attitude, has an indirect positive effect on luxury brand loyalty. Moreover, the interaction between COO technology advancement and product-origin congruency has a significant and positive effect on consumers' brand attitude. Originality/value: This study has tried to investigate the impact of the constructs of the COO image on attitude and loyalty toward luxury brands in Generation Y. It has also dealt with the effect of product-origin congruency on the relationship between each one of the constructs of the COO image and brand attitude.